Адміністративно-правовий статус військовослужбовців в Україні в умовах правового режиму воєнного стану - Коваль, Валерій Петрович; Koval, Valerii Р. (Харків : ХНУ імені В.Н. Каразіна, 2021)
The dissertation is devoted to a comprehensive study of issues related to the administrative and legal status of servicemen under the legal regime of martial law. The legislative regulation of the administrative and legal status of servicemen in Ukraine is studied in the work. Emphasis is placed on the fact that an important aspect in the system of national security and defence in the current conditions of Ukrainian statehood is a clear and detailed regulation of the administrative and legal status of servicemen, including in the direction of regulating the implementation of multifaceted tasks in peacetime as well as within the legal regime of martial law.
Administrative and legal status of servicemen in Ukraine under the legal regime of martial law
В роботі досліджено законодавче регулювання адміністративно-правового статусу військовослужбовців в Україні. Акцентовано увагу на тому, що важливим аспектом у системі забезпечення національної безпеки та оборони у сучасних умовах розвитку української державності є чітка та докладна регламентація адміністративно-правового статусу військовослужбовців, у тому числі у напрямі унормування виконання останніми багатогранних завдань, що покладаються на них як в умовах мирного часу, так і в межах правового режиму воєнного стану.
Keywords: військове законодавство; правовий статус; адміністративно-правовий статус військовослужбовців; правовий режим; особливий правовий режим; правовий режим воєнного стану; трансформація правового статусу; military legislation; legal status; administrative and legal status of servicemen; legal regime; special legal regime; legal regime of martial law; transformation of legal status